2004
DOI: 10.1073/pnas.0403831101
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced autoimmunity, arthritis, and encephalomyelitis in mice with a reduced oxidative burst due to a mutation in the Ncf1 gene

Abstract: The Ncf1 gene was recently identified as a strong regulator of severe arthritis in rat. This finding was surprising, because the disease-promoting allele mediated a lower level of reactive oxygen species in NADPH oxidase-expressing cells. We have now investigated a splice mutation of the Ncf1 gene in B10.Q mice, causing a truncated and nonfunctional Ncf1 protein. We found that the mutated Ncf1 led to a more severe and chronic relapsing collageninduced arthritis. Enhanced IgG and delayed-type hypersensitivity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
372
4
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 322 publications
(403 citation statements)
references
References 40 publications
25
372
4
2
Order By: Relevance
“…Furthermore, our recent studies demonstrated Ncf1 (coding p47 phox subunit of the NA-DPH oxidase complex, which is a multicomponent electron carrier that is responsible for the reduction of oxygen, resulting in the production of ROS) polymorphism as one of the major genetic factors that control arthritis severity and chronicity, regulating autoimmune reactions and impaired tolerance to CII. [27][28][29] In addition, we have also observed a high frequency of arthritis after CII immunization without any adjuvant in a transgenic mice expressing a CII-specific TCR V␤12 chain that recognizes the immunodominant glycosylated CII260Ϫ270 peptide that is dependent on eosinophilic inflammation. 30 Hence, in the present study, we tested various mouse strains using PNiPAAm-CII immunization to find genetic restriction of arthritis development in the absence of a classical adjuvant.…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…Furthermore, our recent studies demonstrated Ncf1 (coding p47 phox subunit of the NA-DPH oxidase complex, which is a multicomponent electron carrier that is responsible for the reduction of oxygen, resulting in the production of ROS) polymorphism as one of the major genetic factors that control arthritis severity and chronicity, regulating autoimmune reactions and impaired tolerance to CII. [27][28][29] In addition, we have also observed a high frequency of arthritis after CII immunization without any adjuvant in a transgenic mice expressing a CII-specific TCR V␤12 chain that recognizes the immunodominant glycosylated CII260Ϫ270 peptide that is dependent on eosinophilic inflammation. 30 Hence, in the present study, we tested various mouse strains using PNiPAAm-CII immunization to find genetic restriction of arthritis development in the absence of a classical adjuvant.…”
mentioning
confidence: 69%
“…Earlier we identified Ncf1 as an arthritis susceptibility gene in rats and mice, 27,28 which provided evidence for the importance of the dysfunctional NADPH oxidase complex and reduced reactive oxygen species (ROS) production in arthritis development. The Ncf1 protein (also known as p47 phox ) is an essential organizing subunit of the NADPH oxidase complex that is responsible for the production of ROS in phagocytic cells (NOX2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 However, the lower levels of Gstm1 and Gstm2 in the congenic strain might play a protective role during the induction phase of CIA, since reduced oxidative burst response has been shown to promote activation of arthritogenic T cells, both in pristane-induced arthritis (PIA) in rats 20 and in CIA in mice. 21 Tspan-2, which is one of the candidates for Cia21, 5 is also a possible candidate for the insulin-dependent diabetes loci 10, Idd10, mapped to the same region. 22 The gene was upregulated in spleen in the Cia5 congenic compared to the parental strain 12 days after immunization.…”
Section: Discussionmentioning
confidence: 99%